Capture and immobilization of African wolves (Canis lupaster) in the Ethiopian Highlands - Gutema, T; Atickem, A; Lemma, A; Bekele, A; Sillero-Zubiri, C; Zinner, D; Farstad, W; Arnemo, J; Stenseth, N (Wildlife Disease Association, 2018)
We captured 14 individual African wolves (Canis lupaster) a total of 16 times in the Ethiopian Highlands in April 2015 and March 2016 by using rubber-lined foothold traps and immobilized them with dexmedetomidine-ketamine. Traps were baited with sheep meat and surveyed every 2 h. Capture efficiency (number of captures per number of visits) was 0.94, and capture rate (number of captures per number of trap nights) was 0.24. Trapped wolves were immobilized with 0.025 mg/kg dexmedetomidine and 8-10 mg/kg ketamine on the basis of respective estimated body mass. Mean (SD) induction times were 3.4 (0.5) min for subadults ( n=4), 3.5 (0.3) min for adult males ( n=4), and 4.7 (1.0) min for adult females ( n=6). Inductions were calm, muscle relaxation was good, and all animals were completely immobilized. Apart from increased rectal temperatures, no major negative side effects were observed. Atipamezole at 10 mg intramuscularly per milligram of dexmedetomidine administered was used for reversal at a mean of 43.5 (7.7) min after administration of dexmedetomidine-ketamine. Recoveries were relatively smooth, and animals were on feet, leaving the site within a mean of 13.6 (3.9) min, after atipamezole administration. Our results indicate that African wolves can be safely captured and immobilized by using rubber-lined foothold traps and dexmedetomidine and ketamine.